2015
DOI: 10.1371/journal.pone.0144980
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Differences between Cochrane and Non-Cochrane Meta-Analyses on the Same Topic: A Matched Pair Analysis

Abstract: BackgroundMeta-analyses conducted via the Cochrane Collaboration adhere to strict methodological and reporting standards aiming to minimize bias, maximize transparency/reproducibility, and improve the accuracy of summarized data. Whether this results in differences in the results reported by meta-analyses on the same topic conducted outside the Cochrane Collaboration is an open question.MethodsWe conducted a matched-pair analysis with individual meta-analyses as the unit of analysis, comparing Cochrane and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 13 publications
5
48
1
2
Order By: Relevance
“…These findings support earlier assumptions by Useem et al [9], who discussed different search strategies and/or inclusion/exclusion of studies as potential explanations for discrepancies. In our study, only 50% of non-Cochrane reviews reported searching and inclusion of studies irrespective of language and only 46% irrespective of status of publication.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These findings support earlier assumptions by Useem et al [9], who discussed different search strategies and/or inclusion/exclusion of studies as potential explanations for discrepancies. In our study, only 50% of non-Cochrane reviews reported searching and inclusion of studies irrespective of language and only 46% irrespective of status of publication.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, in our matched-pair analysis of Cochrane and non-Cochrane reviews we identified, for the first time, inconsistencies in pooled effect estimates between meta-analyses examining the role of physical activity interventions for prevention and treatment of major chronic diseases (Hacke & Nunan, 2019). These results are consistent with those of a recent analysis of pharmacological interventions which showed generally poor overlap of included studies between matched pairs of Cochrane and non-Cochrane reviews [9].…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Non-Cochrane systematic reviews are twice as likely to have positive conclusion statements as Cochrane reviews 4. Furthermore, non-Cochrane reviews, when matched to an equivalent Cochrane review on the same topic, are more likely to report larger effect sizes with lower precision than the equivalent Cochrane review 5. In both cases, these findings may well reflect the extent to which methodological complexity is ignored or sidestepped in poorer quality reviews.…”
Section: Prevalence Of Spin In Clinical Researchmentioning
confidence: 99%